Effects of Liver Fibrosis Progression on Tissue Relaxation Times in Different Mouse Models Assessed by Ultrahigh Field Magnetic Resonance Imaging. (18th January 2017) - Müller, Andreas; Hochrath, Katrin; Stroeder, Jonas; Hittatiya, Kanishka; Schneider, Günther; Lammert, Frank; Buecker, Arno; Fries, Peter
Abstract : Recently, clinical studies demonstrated that magnetic resonance relaxometry with determination of relaxation times T1 and T 2 ⁎ may aid in staging and management of liver fibrosis in patients suffering from viral hepatitis and steatohepatitis. In the present study we investigated T1 and T 2 ⁎ in different models of liver fibrosis to compare alternate pathophysiologies in their effects on relaxation times and to further develop noninvasive quantification methods of liver fibrosis. MRI was performed with a fast spin echo sequence for measurement of T1 and a multigradient echo sequence for determination of T 2 ⁎ . Toxic liver fibrosis was induced by injections of carbon tetrachloride (1.4 mL CCl4 per kg bodyweight and week, for 3 or 6 weeks) in BALB/cJ mice. Chronic sclerosing cholangitis was mimicked using the ATP-binding cassette transporter B4 knockout (Abcb4 - / - ) mouse model. Untreated BALB/cJ mice served as controls. To assess hepatic fibrosis, we ascertained collagen contents and fibrosis scores after Sirius red staining. T1 and T 2 ⁎ correlate differently to disease severity and etiology of liver fibrosis. T 2 ⁎ shows significant decrease correlating with fibrosis in CCl4 treated animals, while demonstrating significant increase with disease severity in Abcb4 - / - mice. Measurements of T1 and T 2 ⁎ may therefore facilitate discrimination between different stages and causes of liver fibrosis.